2017
DOI: 10.1021/acsami.7b00287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Decomposition Properties of CL-20 through Space-Confining in Three-Dimensional Hierarchically Ordered Porous Carbon

Abstract: High energy and low signature properties are the future trend of solid propellant development. As a new and promising oxidizer, hexanitrohexaazaisowurtzitane (CL-20) is expected to replace the conventional oxidizer ammonium perchlorate to reach above goals. However, the high pressure exponent of CL-20 hinders its application in solid propellants so that the development of effective catalysts to improve the thermal decomposition properties of CL-20 still remains challenging. Here, 3D hierarchically ordered poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…4 is the DSC curves of the samples with the heating rate of 5 °C/min. The exothermic peak of CL-20 reached the peak point at 242 °C and then dropped sharply, which was consistent with the thermal decomposition of explosives [ 20 ]. The thermal decomposition of the coated samples can also be seen from the Fig.…”
Section: Resultssupporting
confidence: 69%
“…4 is the DSC curves of the samples with the heating rate of 5 °C/min. The exothermic peak of CL-20 reached the peak point at 242 °C and then dropped sharply, which was consistent with the thermal decomposition of explosives [ 20 ]. The thermal decomposition of the coated samples can also be seen from the Fig.…”
Section: Resultssupporting
confidence: 69%
“…The effects of CL-20 and RDX on basic properties of CMDB propellants were investigated, the major findings could be summarized as follows: 1) The calculations on energetic properties for CL-20/RDX-CMDB propellants showed that energetic properties of propellant with CL-20 were superior to of propellant with RDX. 2) The data on burning rate revealed that with the increase of RDX/CL-20 mass fraction in the propellants, the burning rates at low pressure (2-8 MPa) remained almost the same but differ observably at high pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). With the increase of CL-20 mass fraction in the propellants, the burning rates of propellants could be enhanced significantly, but the burning rates of propellants containing RDX decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Hexanitro hexaazaisowurtzitane (HNIW or CL-20) is superior to hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and cyclo-tetra-methylenetetranitramine (HMX) with respect to density, enthalpy of formation, and oxygen balance [6][7][8][9]. CL-20 has evoked interest as a promising candidate, replacing various energetic compounds such as RDX, HMX and ammonium perchlorate (AP), for realizing the eco-friendly, high-performance, highspecific impulse(Isp), minimum signature propellants for futuristic missiles and space missions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the potential application of the rapid energy release of energetic materials (decomposition, combustion, detonation, etc.) is limited to some special fields,18,20a,24,32 one can actually take advantage of the energy release effect of the energetic materials for synthesizing advanced functional materials . The unique advantage of the deflagration of GO/CL‐20 film is the generation of an HTP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, doping the nitrocellulose (NC) film15a or micron Al particles with GO results in direct laser ignition of the composite film with low initiation threshold and improved combustion property. CL‐20 hosted in 3D carbon matrixes show enhancement in thermal decomposition and lowering of sensitivity 20b. Recently, trinitrotoluene/CL‐20 and cyclotetramethylene‐tetranitramine/CL‐20 cocrystals were used in laser ignition and found that the cocrystallized materials have a shorter onset to gasification than the constituents .…”
Section: Introductionmentioning
confidence: 99%